Curricular training at a phase I clinical trials unit - Leite, Diana Filipa Gomes (2018)
This report describes a curricular training in a Phase I Clinical Trials Unit, Blueclinical Ltd, company with different business areas in clinical research. Regarding clinical research, an overview of the traditional and the new paradigm of pharmaceutical development is present as well Phase I and Bioequivalence clinical trials details, the European and Portuguese regulatory environment. During the training, I participated in nine clinical trial submissions to Portuguese Competent Authorities. I also participated in the conduction of five bioequivalence / bioavailability trials in healthy volunteers, in which I developed competences as clinical trial assistant and project manager. I performed complementary activities at the other business units of Blueclinical, such as Medical Writing and in Quality System Management, which broadened my competences in other areas of clinical research. Throughout the internship I felt a substantial improvement of my personal skills, such as time and tasks management and communications and leadership skills in the context of professional activities. This integrated curricular training in the master course enhanced my understanding of clinical research processes and enlarged my vision of work opportunities. It also allowed me to identify areas of interest that I intend to pursue in order to develop my career namely clinical research project manager.